Significance Analysis of Connections in a Multivariable Mathematical Model of an Unmanned Underwater Vehicle for Common Motion Trajectories; International Journal of Mechanical Engineering and Robotics Research; Vol. 10, iss. 1 - Gaivoronsky (Gayvoronsky) S. A. Sergey Anatolievich (2021, 2021)
Title screen